European Section/Board of Anaesthesiology/European Society of Anaesthesiology consensus statement on competency-based education and training in anaesthesiology. Issue 6 (June 2020) - Shorten, George D.; De Robertis, Edoardo; Goldik, Zeev; Kietaibl, Sibylle; Niemi-Murola, Leila; Sabelnikovs, Olegs
Abstract : N/A: The change from time-based to competency-based medical education has been driven by society's requirement for greater accountability of medical practitioners and those who train them. The European Society of Anaesthesiology and European Section/Board of Anaesthesiology (Anaesthesiology Section of the European Union Medical Specialists) endorse the general principles of competency-based medical education and training (CBMET) outlined by the international competency-based medical education collaborators. A CBMET curriculum is built on unambiguously defined learning objectives, each of which offers a measurable outcome, amenable to assessment using valid and reliable tools. The European training requirements laid out by the European Board of Anaesthesiology define four 'Generic Competences', namely expert clinician, professional leader, academic scholar and inspired humanitarian. A CBMET programme should clearly document core competencies, defined end-points, proficiency standards, practical descriptions of teaching and assessment practices and an assessment plan. The assessment plan should balance the need to provide regular, multidimensional formative feedback to the trainee with the need to inform high stakes decisions. A trainee who has not achieved a proficiency standard should be provided with an individualised training plan to address specific competencies or deficits. Programme formats will inevitably differ given the constraints of scale and resource that apply in different settings. The resources necessary to develop and maintain a CBMET programme in anaesthesiology include human capital, access to clinical learning opportunities, information technology and physical infrastructure dedicated to training and education. Simulation facilities and faculty development require specific attention. Reflective practice is an important programme element that supports wellbeing, resilience and achievement of professional goals. CBMET programmes should enable establishment of a culture of lifelong learning for the anaesthesiology community. Abstract : Supplemental Digital Content is available in the text